2011
DOI: 10.1107/s0909049511027488
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of angular distribution of soft X-ray radiation from thin targets in the tabletop storage ring MIRRORCLE-20SX

Abstract: The only available tabletop electron storage rings are the machines from the MIRRORCLE series. The electrons are accelerated in a microtron and injected into the storage ring. During its circulation, each electron passes through a tiny target many times, emitting a photon beam. Both the spectrum and the angular distribution of the radiation depend on the material, the thickness and the shape of the target. In this paper measured angular distributions of the radiation from several different targets in the magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Among the recent experimental studies, the results that was observed on the inner electron beam of the special synchrotron "MIRRORCLE-20" [19] are of particular interest. In this experimental studies, an anomalously high angular density of soft X-ray radiation was observed in the plane perpendicular to the magnetic field of the synchrotron.…”
Section: Jinst 16 P07043mentioning
confidence: 99%
“…Among the recent experimental studies, the results that was observed on the inner electron beam of the special synchrotron "MIRRORCLE-20" [19] are of particular interest. In this experimental studies, an anomalously high angular density of soft X-ray radiation was observed in the plane perpendicular to the magnetic field of the synchrotron.…”
Section: Jinst 16 P07043mentioning
confidence: 99%
“…For example, the experimental Cherenkov angles for carbon and Si turned out to be the same, which does not agree with the theory. Among the recent experimental studies, the results that was observed on the inner electron beam of the special synchrotron "MIRRORCLE-20" [19] are of particular interest. In this experimental studies, an anomalously high angular density of soft X-ray radiation was observed in the plane perpendicular to the magnetic field of the synchrotron.…”
Section: Introductionmentioning
confidence: 99%
“…We are concerned on Compton back scattering using a storage ring, [1] but we sought that monochromatic X-ray is not useful for spectroscopy, or protein crystallography. We choose the mechanisms using the collision of relativistic electron and target such as Bremsstrahlung [2] for hard X-ray or synchrotron Cherenkov radiation [3] for soft X-ray. MIRRORCLE-CV series is an X-ray source based on a low-energy electron storage ring.…”
Section: Introductionmentioning
confidence: 99%